Delamination effect modeling, simulation and experimental validation of lap shear test - Syed Muhammad, Kashif (Universiti Malaya, 2012)
Single lap joint is among the most widely used adhesively bonded joint type for both non-structural and structural applications. Considering the strength and efficiency of such joint, good understanding of the adhesive behavior and stress analysis of the joint is very important, especially for the overlapped bonded area in the lap joint. Apparent shear strength of adhesively bonded single lap joint is studied and Finite element analysis (FEA) of lap shear test is investigated using ANSYS software. Regarding adhesively bonded structures, the novelty of the present work lies in the study and discussion of the modeling and simulation approaches of interface delamination effect. Finally, an experimental verification of the simulated results is presented and discussed. Here, it is shown that the use of interface elements using cohesive zone model is best suited to predict the failure initiation and delamination pattern of such an adhesive joint.